Analysis of Australia's TPPA on Intellectual Property Rights Protection Under TRIPS and WTO - Yustisio, Rifki; Riyandono, Aji Yudo (Pustaka Peradaban, 2024)
Intellectual Property Rights (IPR) in the international trade law system are regulated through several international agreements, including the provisions of Trade-Related Aspects of Intellectual Property Rights (TRIPS) and the General Agreement on Tariffs and Trade (GATT). The main objectives of international trade law are to maintain stability in global trade, prevent domestic policies that harm other countries, create a conducive and favorable trade climate for economic growth, and improve the standard of living of people globally. This research uses normative legal methods with statutory and conceptual approaches. This study focuses on the Tobacco Plain Packaging Act (TPPA) policy enacted by Australia. This policy is based on the Framework Convention on Tobacco Control (FCTC) issued by the World Health Organization (WHO) to reduce tobacco consumption. However, this policy conflicts with TRIPS principles related to IPR protection, particularly trademarks. The TPPA restricts the use of trademarks on tobacco packaging, by setting standards by prohibiting the inclusion of trademarks or other marks on tobacco product packaging, using standardized fonts, and requiring the use of uniform packaging for all tobacco products sold in Australia, by specifying color, shape, size, and layout. This is considered to be contrary to TRIPS principles, which protect trademark rights as part of non-discriminatory international trade. Nonetheless, under GATT Article 20 on General Exceptions, Australia's TPPA policy is considered legitimate as it aims to protect human life or health in formulating national laws in the public interest.